Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\)
\(2x\left(x-3\right)-\left(3-x\right)=0\)
\(\Leftrightarrow2x\left(x-3\right)+\left(x-3\right)=0\)
\(\Leftrightarrow\left(2x+1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x+1=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{-1}{2}\\x=3\end{cases}}\)
\(2,\)
\(3x\left(x+5\right)-6\left(x+5\right)=0\)
\(\Leftrightarrow\left(3x-6\right)\left(x+5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x-6=0\\x+5=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-5\end{cases}}\)
\(3,\)
\(x^4-x^2=0\)
\(\Leftrightarrow x^2\left(x^2-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x^2=0\\x^2-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm1\end{cases}}\)
\(4,\)
\(x^2-2x=0\)
\(\Leftrightarrow x\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}\)
\(5,\)
\(x\left(x+6\right)-10\left(x-6\right)=0\)
\(\Leftrightarrow x^2+6x-10x+60=0\)
\(\Leftrightarrow x^2-4x+60=0\)
\(\Leftrightarrow x^2-4x+4+56=0\)
\(\Leftrightarrow\left(x-2\right)^2=-56\)(Vô lý)
=> Phương trình vô nghiệm
![](https://rs.olm.vn/images/avt/0.png?1311)
1: =>(x+3)(x-5)=0
=>x=5 hoặc x=-3
2: =>(x-1)(5x-1)=0
=>x=1/5 hoặc x=1
5: =>(x-4)*x=0
=>x=0 hoặc x=4
10: =>(x+5)(x-3)=0
=>x=3 hoặc x=-5
9: =>(x-2)(x-4)=0
=>x=2 hoặc x=4
7: =>(x-6)(2x-1)=0
=>x=1/2 hoặc x=6
8: =>(2x-1)(3x-12)=0
=>x=4 hoặc x=1/2
![](https://rs.olm.vn/images/avt/0.png?1311)
Answer:
\(\left(2x-3\right).\left(x+1\right)-x.\left(2x+3\right)-9=0\)
\(\Rightarrow\left(2x^2+2x-3x-3\right)-2x^2-3x-9=0\)
\(\Rightarrow\left(2x^2-x-3\right)-2x^2-3x-9=0\)
\(\Rightarrow2x^2-x-3-2x^2-3x-9=0\)
\(\Rightarrow\left(2x^2-2x^2\right)-\left(x+3x\right)-\left(3+9\right)=0\)
\(\Rightarrow-4x-12=0\)
\(\Rightarrow x+3=0\)
\(\Rightarrow x=-3\)
\(2x.\left(x-3\right)-x+3=0\) (Sửa đề)
\(\Rightarrow2x.\left(x-3\right)-\left(x-3\right)=0\)
\(\Rightarrow\left(x-3\right).\left(2x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\2x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=3\\2x=1\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=\frac{1}{2}\end{cases}}}\)
\(2x.\left(x^2-4\right)+6.\left(4-x^2\right)=0\)
\(\Rightarrow2x.\left(x^2-4\right)-6.\left(x^2-4\right)=0\)
\(\Rightarrow2.\left(x-3\right).\left(x+2\right).\left(x-2\right)=0\)
Trường hợp 1: \(x-3=0\Rightarrow x=3\)
Trường hợp 2: \(x+2=0\Rightarrow x=-2\)
Trường hợp 3: \(x-2=0\Rightarrow x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x - 7) + 17 = 6
=> 2x - 7 = 6 - 17
=> 2x - 7 = -11
=> 2x = -11 + 7
=> 2x = -4
=> x = -4 : 2
=> x = -2
+) 12 -2(3 - 3x)= -2
=> 2(3 - 3x) = 12 + 2
=> 2(3 - 3x) = 14
=> 3 - 3x = 14 : 2
=> 3 - 3x = 7
=> 3x = 3 - 7
=> 3x = -4
=> x = -4/3
\(\left(x+1\right)\left(x-3\right)=0\)
=> \(\orbr{\begin{cases}x+1=0\\x-3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-1\\x=3\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 3x(x-2)-x+2=0
3x(x-2)-(x-2)=0
(3x-1)(x-2)=0
=>\(\hept{\begin{cases}3x-1=0\\x-2=0\end{cases}}\)
=> \(\hept{\begin{cases}3x=1\\x=2\end{cases}}\)
=>\(\hept{\begin{cases}x=\frac{1}{3}\\x=2\end{cases}}\)
vậy x thuộc (1/3;2)
![](https://rs.olm.vn/images/avt/0.png?1311)
`(x+2)(x^2 -2x+4) -x(x^2-2)=15`
`<=> x^3 +8 - x^3 + 2x-15=0`
`<=> 2x-7=0`
`<=> 2x=7`
`<=>x=7/2`
__
`(x-4)^2 -(x-2)(x+2)=6`
`<=>x^2 - 8x+16- x^2 +4-6=0`
`<=> -8x+14=0`
`<=> -8x=-14`
`<=>x=14/8= 7/4`
__
`x^4 -2x^3 +x^2-2x=0`
`<=>x(x^3-2x^2+x-2)=0`
`<=> x(x^3+x-2x^2-2)=0`
`<=>x(x(x^2+1) -2(x^2+1))=0`
`<=> x(x^2+1)(x-2)=0`
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2+1=0\\x-2=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
a) \(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x^2-2\right)=15\)
\(\Leftrightarrow\left(x^3+2^3\right)-\left(x^3-2x\right)=15\)
\(\Leftrightarrow x^3+8-x^3+2x=15\)
\(\Leftrightarrow2x+8=15\)
\(\Leftrightarrow2x=15-8\)
\(\Leftrightarrow2x=7\)
\(\Leftrightarrow x=\dfrac{7}{2}\)
b) \(\left(x-4\right)^2-\left(x+2\right)\left(x-2\right)=6\)
\(\Leftrightarrow x^2-8x+16-\left(x^2-4\right)=6\)
\(\Leftrightarrow x^2-8x+16-x^2+4=6\)
\(\Leftrightarrow-8x+20=6\)
\(\Leftrightarrow-8x=6-20\)
\(\Leftrightarrow-8x=-14\)
\(\Leftrightarrow x=\dfrac{7}{4}\)
c) \(x^4-2x^3+x^2-2x=0\)
\(\Leftrightarrow x^3\left(x-2\right)+x\left(x-2\right)=0\)
\(\Leftrightarrow\left(x^3+x\right)\left(x-2\right)=0\)
\(\Leftrightarrow x\left(x^2+1\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x+\left(1+2+3+...+100\right)=15150\)
\(2x+\left[\left(1+100\right)+\left(2+99\right)+...+\left(50+51\right)\right]=15150\)
\(2x+\left[101+101+...+101\right]=15150\)CÓ 50 SỐ 101
\(2x+\left[101\times50\right]=15150\)
\(2x=15150:5050\)
\(2x=3\)
\(x=3:2\)
\(x=1.5\)
a, 2x + (1+2+3+4+...+100) = 15150
=> 2x + \(\frac{\left(1+100\right).\left[\left(100-1\right)+1\right]}{2}\)= 15150
=> 2x + \(\frac{101.100}{2}\)= 15150
=> 2x + 5050 = 15150
=> 2x = 15150 - 5050
=> 2x = 10100
=> x = 10100 : 2
=> x = 5050
Vậy x = 5050
b, .(x+1)+(x+2)+(x+3)+(x+4)+(x+5)+(x+6)+(x+7)+(x+8)=36
=> (x + x + x + x +x + x +x +x ) + (1 + 2 + 3 + 4 + 5 + 6 + 7 + 8) = 36
=> 8x + 36 = 36
=> 8x = 0
=> x = 0
Vậy x = 0
c, 0+0+4+6+8+...+2x=110
Sửa đề :0 + 2 + 4 + 6 + 8 + ... + 2x = 110 = 2 + 4 + 6 + 8 + ... + 2x = 110
SSH : \(\frac{\left(2\text{x}-2\right)}{2}+1=x-1+1=x\)
Tổng : \(\frac{\left(2\text{x}+2\right).x}{2}=110\Leftrightarrow\frac{2.\left(x+1\right).x}{2}=110\)
\(\Leftrightarrow\left(x+1\right)x=110\)
\(\Leftrightarrow\left(10+1\right).10=110\)
=> x = 10
Vậy x = 10